The Effects of Liquidity Risk and Interest-Rate Risk on Profitability and Firm Value among Banks in ASEAN-5 Countries - Ebenezer, Olalere Oluwaseyi; Islam, Md. Aminul; Yusoff, Wan Sallha; Rahman, Shafiqur (Journal of Reviews on Global Economics, 2019)
This study explores the issues relating to liquidity risk and interest-rate risk, recognizing that existing studies are mostly vague in emerging and developing markets. Panel data estimation technique is employed in the study based on data extracted from 63 commercial banks in ASEAN-5 countries over the period 2009 to 2017 making up to 567 observations. The empirical results reveal that loan to deposit ratio have a positive significant effect on firm value while liquid asset ratio, interest rate risk (net interest margin and asset interest yield) have a negative significant effect on firm value for ASEAN. The loan to deposit ratio have a positive significant impact on return on asset, interest rate risk and banks size have a significant negative effect on return on asset for ASEAN banks while GDP and inflation have a positive significant effect on return on asset. Also, the liquidity risk have a negative significant effect on return on equity while the interest rate risk have a positive significant effect, bank size have a significant negative effect on return on equity while inflation rate have a positive significant impact on return on equity. Hence, this empirical study provides implications that emphasizes on the need for banks to adhere to prudential and regulatory guidelines and ensure corporate management with respect to liquidity exposure that is capable of critically affecting banks profitability and firm value. The dynamics of interest rate volatility in banks operating environment necessitates that financial institutions use sound risk management practices in order to obtain higher valuations, achieve better financial performance and experience diminished costs of financial distress that’s useful for policy implementations in ASEAN economies and suggest that further study can explore the interaction between abnormal loan growth and non-performing loans with a robust econometrics model.